Tìm x biết: c) 2x mũ 2 + 3(x – 1)(x + 1) = 5x(x + 1); d) (8 – 5x)((x + 2) + 4(x – 2)(x + 1) + (x – 2)(x + 2); e) 4(x – 1)( x + 5) – (x +2)(x + 5) = 3

Question

Tìm x biết:
c) 2x mũ 2 + 3(x – 1)(x + 1) = 5x(x + 1);
d) (8 – 5x)((x + 2) + 4(x – 2)(x + 1) + (x – 2)(x + 2);
e) 4(x – 1)( x + 5) – (x +2)(x + 5) = 3(x – 1)(x + 2).

in progress 0
Genesis 3 tháng 2021-09-19T18:57:47+00:00 2 Answers 6 views 0

Answers ( )

    0
    2021-09-19T18:59:15+00:00

    Đáp án:

     

    Giải thích các bước giải:2x^2 +3x^2-3=5x^2 +5x

    5x^2-3=5x^2+5x

    5x=-3

    x=-3/5

    b)khong co dau bang

    c)4x^2+16x-20-x^2-7x=3x^2+3x-6

    3x^2 + 9x – 20=3x^2 +3x -6

    6x=14

    x=7/3

     

    0
    2021-09-19T18:59:36+00:00

    Giải thích các bước giải:

    c, 2x²+3(x-1)(x+1)= 5x(x+1)

    ⇔2x²+3(x²-1)=5x²+5x

    ⇔2x²+3x²-3=5x²+5x

    ⇔2x²+3x²-5x²-5x=3

    ⇔-5x=3

    ⇔x=-3/5  

    Vậy x=-3/5

    d, (8-5x)(x+2)+4(x-2)(x+1) +(x-2)(x+2)

    =8x+16-5x²-10x+4x²-4x-8+x²-4

    = -6x+4

    e, 4(x-1)(x+5)-(x+2)(x+5)= 3(x-1)(x+2)

    ⇔4x²+20x-4x-20-x²-5x-2x-10=3x²+6x-3x-6

    ⇔4x²+20x-4x-x²-5x-2x-3x²-6x+3x= 20+10-6

    ⇔6x=24

    ⇔x=4

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )